Designing A Web-Based Content-Based Filtering Method for A Culinary Marketplace - Shiddiq, Zulfikar; Suendri, Suendri; Sibarani, Fathiya Hasyifah (International Journal of Engineering and Computer Science Applications (IJECSA), 2025)
The development of information technology has made various aspects of life easier, including product marketing through marketplace applications. In Pasar Bengkel Village, known as a culinary center, vendors have experienced a decline in the number of customers due to the operation of the Medan–Tebing Tinggi toll road, which has reduced visitor traffic. The purpose of this study is to design a marketplace application with a recommendation system that can help vendors increase product visibility and attract customers back. The research method is the application of a Content-Based Filtering-based recommendation system with the Term Frequency–Inverse Document Frequency (TF-IDF) algorithm to process product description data and generate relevant recommendations for users. The result of this study is a marketplace application that is able to provide personalized product recommendations based on the frequency of word occurrences in product descriptions using the TF-IDF technique. In conclusion, this application is expected to be an innovative solution in increasing the competitiveness of local culinary vendors by expanding their marketing reach and maintaining the sustainability of their businesses..